Dynamics in ownership and firm survival: evidence from corporate Germany - Florian Heiss; Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This study investigates the determinants of changes in corporate ownership and firm failure, taking into account different types of sellers and buyers of control blocks. For a large panel of German corporations we find that firms are more likely to fail or to be sold when performance is poor, financial pressure is high, and firm size is small. Cross ownership deters control changes, and ownership concentration has a non-linear impact on the likelihood of control transfer. In contrast to corporate shareholders, private shareholders tend to sell control blocks when financial pressure increases.
Keywords: G34; G33; G32; 330; Corporate governance; ownership structure; bankruptcy; takeover; Unternehmensentwicklung; Konkurs; Übernahme; Eigentümerstruktur; Corporate Governance; Schätzung; Deutschland